Drought effects on water relation and growth performance of rubber (Hevea brasiliensis) / Che Ku Hasidayati Che Ku Mohd Salleh - Che Ku Mohd Salleh, Che Ku Hasidayati (Faculty of Plantation and Agrotechnology, 2016)
Rubber is tropical tree crop which is mainly grown for the industrial production of latex. The lack of available land and competition with other crop such as mainly oil palm, rubber plantations are being extended to drought-prone areas that provide sub-optimal growing conditions for rubber tree cultivation where there is along dry season. Although water is the most abundant molecule on the earth's surface, the availability of water is the factor that most strongly restricts terrestrial plant production on a global scale. Low water availability limits the productivity of many natural ecosystems, particularly in dry climates. The outcome of this study is to enhance knowledge about performance growth and response of rubber crop on drought stress. The review study conducted by the past research paper and other particular resources is necessary.